The adenoids hyperplasia and adenotomy effects on the children's immunity and health - L.S. Ovcharenko; V.Yu. Tkachenko; A.A. Vertegel; I.V. Samokhin; A.V. Kryazhev; T.G. Andrienko; D.N. Sheludko (Zaslavsky O.Yu., 2017)
The current literature review presents data of adenoids hyperplasia and adenotomy effect on the children's immunity and health. The presence of adenoid hyperplasia in a child was found to provide conditions for higher prevalence of severe respiratory pathology due to prolonged colonization by pathogenic and opportunistic microorganisms against the background of morpho-functional rearrangement of mucosal immunity structures with its transient insufficiency. Adenotomy has a positive effect only as a means of eliminating mechanical obstructions to nasal breathing, without affecting other components of the pathological process in the nasopharynx of children with adenoid hyperplasia.